2022
DOI: 10.3389/fpubh.2022.1000953
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle choices mediate the association between educational attainment and BMI in older adults in China: A cross-sectional study

Abstract: As the Chinese population ages, unhealthfully high body mass index (BMI) levels in older adults are becoming a public health concern as an unhealthfully high BMI is an ill-being condition and can contribute to the risk of disease. Education and lifestyle choices affect BMI; however, the evidence on the relationships and interactions among these factors remains unclear. This study aimed to investigate the mediating effect of lifestyle choices on educational attainment and BMI among older adults in China. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The present study demonstrated a 43% reduction in the risk of phlebitis for every 1 SD increase in EA, data that have not been similarly reported. Previous observational studies have focused more on the fact that higher EA is associated with a lower risk of obesity and its traits (including body mass index, basal metabolic rate, waist circumference, and waist-to-hip ratio), [11][12][13][14][15][16][17] and that obesity and its traits were also the risk factors for VV, VTE, and phlebitis, 8,9,[19][20][21][22] which is in line with the results of the present study, which, however, further uncovered the importance of hip circumference in the mediator pathway, which has been given less attention. Previous studies have failed to systematically assess the important role of obesity and its traits in the pathway of the effect of EA on the risk of VV, VTE, and phlebitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study demonstrated a 43% reduction in the risk of phlebitis for every 1 SD increase in EA, data that have not been similarly reported. Previous observational studies have focused more on the fact that higher EA is associated with a lower risk of obesity and its traits (including body mass index, basal metabolic rate, waist circumference, and waist-to-hip ratio), [11][12][13][14][15][16][17] and that obesity and its traits were also the risk factors for VV, VTE, and phlebitis, 8,9,[19][20][21][22] which is in line with the results of the present study, which, however, further uncovered the importance of hip circumference in the mediator pathway, which has been given less attention. Previous studies have failed to systematically assess the important role of obesity and its traits in the pathway of the effect of EA on the risk of VV, VTE, and phlebitis.…”
Section: Discussionmentioning
confidence: 99%
“…8 Lower educational attainment (EA) and socioeconomic status have been found to be associated with an increased risk of vascular disease (such as VTE 9 ) in a global context. 10 Observational studies have suggested that higher EA was protective against obesity 11 and obesity-related traits such as body mass index, 12,13 waist circumference, 14,15 and waistto-hip ratio, 15,16 and was also independently associated with the basal metabolic rate 17 and that there may be an interconnection between these traits as well. [16][17][18] Obesity was considered the risk factor for VV due to its contribution to elevated central venous pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Another possibility is that there may exist a non-linear relationship between BMI and education, which would not be captured by standard multivariable regression analysis ( 52 ). Furthermore, it is important to take into account factors such as diet and levels of physical activity that may influence the relationship between BMI and education ( 53 ). In summary, while our analysis did not find a significant correlation between education and BMI, this does not conclusively disprove a potential relationship.…”
Section: Discussionmentioning
confidence: 99%
“…To distinguish different age stages, we divided every 5 years from 20 to 40 years old into one category. According to the Chinese classification, BMI values of <18.5 kg/m 2 , 18.5 ≤ BMI <24 kg/m 2 , 24 ≤ BMI <28 kg/m 2 , and BMI≥28 kg/m 2 represent underweight, normal weight, overweight, and obesity, respectively ( 15 ). Defecation posture refers to the posture that a woman adopted for most of her defecations and is categorized according to the potential impact on the PFM as squatting posture, sitting posture, or not specified ( 16 ).…”
Section: Methodsmentioning
confidence: 99%